Improved determination of selenium in plant and peat samples using hydride generation-atomic fluorescence spectrometry (HG-AFS) - Barciela García, Julia; Krachler, Michael; Chen, Bin; Shotyk, William (Analytica chimica acta, 2005)
A robust, accurate and sensitive analytical procedure for the determination of Se in plant and peat samples by hydride generation-atomic fluorescence spectrometry (HG-AFS) was developed. Aliquots (200mg) of dried samples were digested with 3mL nitric acid and 0.5mL hydrogen peroxide in closed, pressurized PTFE vessels in a microwave oven at 220°C. Addition of HBF4 or HF to the digestion mixture was not required because experiments demonstrated that Se was not hosted in the silicate fraction of the investigated sample matrices. Selenium(VI) was directly reduced to Se(IV) in the undiluted digestion solutions after addition of 3.8mL of 4M HCl in a microwave oven at 103°C for 3min. Other reduction reagents, such as hydroxylamine hydrochloride or urea, were not necessary to cope with potential interferences from nitrogen oxides that could hamper the reliable determination of Se by HG-AFS. Optimum hydride generation of Se was achieved by using 0.9% NaBH4 and 4.5M HCl. A solution detection limit of 11ngL−1 was obtained under the optimized experimental conditions which corresponds to a method detection limit of 2.8ngg−1 in solid peat and plant materials. The precision of replicate measurements was better than 3% at Se concentrations of 50ngL−1. The analytical procedure was critically evaluated by analysing two certified plant reference materials (SRM 1515 Apple Leaves and SRM 1547 Peach Leaves) as well as three peat reference materials. Excellent agreement between the experimental values ranging from 50ngg−1 to ∼2μgg−1 and the certified concentrations was obtained.